Спростить вираз (2a – 3)² + (3 -2a)(3 +2a) -3(a+2)(3a – 1)

sasha123123476 sasha123123476    1   06.09.2021 15:49    0

Ответы
burdyugova48 burdyugova48  25.11.2021 05:30

(2a-3)^2+(3-2a)(3+2a)-3(a+2)(3a-1)=\\\\2^2a^2-2*2a*3+3^2+3^2-2^2a^2+(-3a+2*(-3))(3a*(-3)-1*(-3))=\\\\=4a^2-12a+9+9-4a^2+(-3a-6)(-9a+3)=\\\\-12a+18-3a*(-9a)-3a*3-6*(-9a)-6*3=\\\\-12a+18+27a^2-9a+54a-18=-12a+27a^2+45a=27a^2+33a

формула квадрата разности ⇒ ( a - b )² = a² - 2ab + b²

( 2a - 3 )² = 2²a² - 2 × 2a × 3 + 3² = 4a² - 12a + 9

формула разности квадратов ⇒ ( a - b )( a + b ) = a² - b²

( 3 - 2a )( 3 + 2a ) = 3² - 2²a² = 9 - 4a²

-3( a + 2 )( 3a - 1 ) = ( -3a + 2 × (-3) )( 3a × (-3) - 1 × (-3) ) = ( -3a - 6 )( -9a + 3 )=

= -3a × (-9a) - 3a × 3 - 6 × (-9a) - 6 × 3 = 27a² - 9a + 54a - 18 = 27a²+45a-18

4a² - 12a + 9 + 9 - 4a² + 27a² + 45a - 18 = 27a² + 45a - 12a + 9 + 9 - 18 =

= 27a² + 33a + 18 - 18 = 27a² + 33a

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра